Malaria Chemoprophylaxis and Self‐Reported Impact on Ability to Work: Mefloquine Versus Doxycycline. Issue 6 (1st October 2015) - Terrell, Andrew G.; Forde, Mike E.; Firth, Richard; Ross, David A.
Abstract : Background: It is well known that both mefloquine and doxycycline are commonly associated with adverse effects when taken for malaria chemoprophylaxis. However, the relative impact of these on travelers' ability to work is not so well understood. The aim of this study was to identify which drug has a lesser impact on the ability to work as measured by self‐reported severity of adverse effects via a questionnaire. Methods: This was a questionnaire‐based two‐arm cohort study. Participants were soldiers selected from 10 consecutive units training in Kenya during 2012 and 2013. The exposure was either doxycycline or mefloquine and the main outcome measure was impact upon ability to work. Each cohort was advised to take doxycycline or mefloquine with exceptions at the individual level where medically or occupationally advised. Results: Significantly more ( p < 0.0001) doxycycline users reported that one or more adverse effects had interfered with their ability to do their job than mefloquine users. Of the 867 mefloquine users, who reported on the impact of adverse effects, 109 (12.6%) reported that one or more adverse effects had impacted upon their ability to do their job, compared to 152 (22.2%) of the 685 doxycycline users who had reported on the impact of any adverse effects. Doxycycline symptoms were predominantly gastrointestinal and dermatological, whereas mefloquine symptoms were neuropsychiatric. Conclusions: Self‐reported symptoms were common in those that responded and, while the true background rate of adverse effects (off any medication) is unknown, doxycycline had a significantly increased rate compared with mefloquine and was associated with a greater occupational impact. Therefore, this study supports the view that, for organizations which provide malaria chemoprophylaxis to employees free of charge, mefloquine should be the first‐choice antimalarial drug where the only alternative is doxycycline.